Reward Systems on Employee Performance in commercial Bank: Mediating role of Job Satisfaction - Kaphle, Deepak Prasad; Sapkota , PadmaRaj (Jana Adarsha Research Journal, 2026)
This research investigates the effect of reward systems on job satisfaction and performance of employees in commercial banks of Chitwan, Nepal. Praise includes monetary rewards like salary, bonuses and non monetary rewards including recognition, career growth, training, and work-life balance. This studied for their effects on employee motivation and productivity. A descriptive and correlational research design was followed for the study. Primary data from 135 employees in ten commercial banks were collected through the use of a structured questionnaire and analyzed using SPSS. The results showed that economic rewards (Mean = 3.56, SD = 0.920) were one of the main reasons for job satisfaction. The performance-based incentives (Mean = 3.77, SD = 0.977) along with recognition, turned out to be significantly encouraging to employees’ performance. There was a significant positive correlation between job satisfaction and job performance: r = 0.399, p < 0.001. The effective reward system has improved morale as well as efficiency. There is a comprehensive to tal reward framework will contain both intrinsic and extrinsic rewards. This study may help enhance employee retention, improve employee engagement, and finally, organizational competitiveness in Nepalese banking.